Levelized Cost of Electricity for Wind-Solar Power Systems in Japan, a Review - Jahangiri, Mehdi; Akbar Alidadi Shamsabadi; Riahi, Rashid; Raeiszadeh, Farhad; Pezhman Fazeli Dehkordi (Journal of power technologies, 2020)
To date no technical-economic-environmental review has been carried out on the use of hybrid wind-solar power plants in Japan. The study reported in this paper used HOMER software to analyze the electricity supply from renewable energy systems at 198 stations in Japan. The ranges of wind speed and solar radiation of the locations are 1.6-12 m/s and 2.723-5.435 kWh/m2-day, respectively. The results show that the average, maximum and minimum use of renewable energy in Japan are 96.2%, 100% and 89%, respectively. Also, the average, maximum and minimum cost per kWh of energy are $ 0.434, $ 0.526, and $ 0.249, respectively. The cheapest wind turbine system (the cheapest renewable energy system), the cheapest solar system, the cheapest hybrid wind-solar system, and the most expensive hybrid system, have a price per kWh of energy $ 0.294, $ 0.349, $ 0.339 and $ 0.526, respectively. These systems are located at Fuji Mountain, Minamitorishima, Iwojima and Tokyo, respectively.